(untitled) (Journal of Informatics Education and Research, 2025)
EdTech, or unconventional educational technologies, is changing the way knowledge is delivered, accessed, and experienced in a time of educational change. EdTech platforms utilize adaptive content delivery and personalized learning pathways to create learner-centric experiences that cater to the various needs of both educators and students. This study explores how strategic marketing and individualized instruction promote engagement and adoption by comprehending the dynamics of consumer behaviour and market trends. This study explores how consumer preferences, marketing tactics, and technological innovation interact, highlighting the critical role influencers play in fostering trust and advancing EdTech platforms. Data from 200 respondents was analysed using multimedia-enhanced questionnaires and structured surveys to find important trends. While adaptive content delivery increased satisfaction by matching educational experiences with individual learner preferences, personalized learning pathways were found to increase user engagement. The influencers have become influential trust-builders in the adoption of EdTech platforms by developing authentic engagement with end users. Further, the research shows concerns such as inclusion and digital divide, requiring pertinent and long-term solutions that ensure equal access to education. By integrating user-centric tactics via influencer-driven mechanisms, adaptive delivery methods, and personalized learning systems, it is possible for EdTech companies to enhance the satisfaction of their users while simultaneously democratizing education. This report presents action guidelines to the educators, developers, and marketers who desire to align a new technology with shifting student demands for an innovative, inclusive, and influential learning future. Keywords: EdTech, Unconventional Education, Market Analysis, Consumer Behaviour, Marketing Strategies, Case Studies.